Systems simulation in agriculture - Dent, J. B.; Blackie, M. J.; Harrison, S. R. (London : Applied Science Publishers, 1979)
The book is based on the premise that a computer-based simulation model is an integral part of systems research because it can provide the framework for guiding agricultural experiments, accumulating and assessing results of these experiments, and assisting decision makers in controlling the system being modelled. Consequently, this book is concerned with construction and operation of computer-based simulation models. Throughout, the authors intertwine examples from two simulation models with which they have had earlier association. One is a barley-leaf-rust model; the other is a pig-herd management model. A chapter devoted to model construction includes a discussion of a difficult problem in any area of scientific endeavour-where to begin.
Includes bibliographical references and index.
lje 22/01/2019
Loans
Keywords: Agriculture; Computer simulations; System analysis